Postrelapse MS Treatment with Alemtuzumab Better than SC IFN-β-1a - Hoyle, Brian (MD Conference Express, 2014)
Subgroup analyses, entitled An Extension Protocol for Multiple Sclerosis Patients Who Participated in Genzyme-Sponsored Studies of Alemtuzumab [NCT00930553; Barkhof F et al. ACTRIMS/ECTRIMS 2014 (poster P075)], of an ongoing, open-label extension of the Comparison of Alemtuzumab and Rebif Efficacy in Multiple Sclerosis, Study Two [CARE-MS II; Coles AJ et al. Lancet. 2012], have confirmed the superiority of treatment of MS using the anti-CD52 humanized monoclonal antibody, alemtuzumab, over subcutaneous interferon beta-1a (SC IFN-β-1a) in magnetic resonance imaging (MRI) outcomes.